Local and systemic signaling of iron status and its interactions with homeostasis of other essential elements - Gayomba, Sheena R.; Zhai, Zhiyang; Jung, Ha-il; Vatamaniuk, Olena K. (Frontiers in Plant Science, 2015)
Iron (Fe) is essential for plant growth and development. However, alkaline soils, which occupy approximately 30% of the world’s arable lands, are considered Fe-limiting for plant growth because insoluble Fe (III) chelates prevail under these conditions. In contrast, high bioavailability of Fe in acidic soils can be toxic to plants due to the ability of Fe ions to promote oxidative stress. Therefore, plants have evolved sophisticated mechanisms to sense and respond to the fluctuation of Fe availability in the immediate environment and to the needs of developing shoot tissues to preclude deficiency while avoiding toxicity. In this review, we focus on recent advances in our understanding of local and systemic signaling of Fe status with emphasis on the contribution of Fe, its interaction with other metals and metal ligands in triggering molecular responses that regulate Fe uptake and partitioning in the plant body.